Interferências rítmicas do português brasileiro no inglês como L2: o choque acentual - Junior, Leônidas José da Silva (2013)
This dissertation aims to analyze how Stress Clash - a phenomenon in which two syllables bearing primary stress are adjacent in different words forming a phonological phrase such as [maRÉ BRAva] (high tide) produced during the phonetic realization of English as a second language by native speakers of Brazilian Portuguese (BP) and what strategies are used to solve these clashes. The aim of this dissertation is also to show, from database and acoustic analysis as well as autosegmental fonology, that the rhythm of Brazilian Portuguese causes interference / influence when the speaker of BP as mother-tongue speaks English and such that, if we analyze pronunciation and fluency in English as second language, we must give emphasis to the rhythmic aspects of the language. As a bottom line, we shall set parameters in which the concepts and postulates about pronunciation and acquisition of phoneticphonological aspects of English we need to rely upon. Stress clash, both in English and Brazilian Portuguese, is mostly solved by native speakers of BP through the so-called Silent demibeat strategy regardless of syntactic or prosodic uniformity factors as well as phonological re-operationalization such as assimilation; resyllabification and other sandhi processes. These processes characterize phonological interference or influence from the rhythm of BP in the realization of post-lexical events in English what defines therefore a dichotomy between rhythmic features of these two languages. Data of five informants - three Brazilians and two Americans - were recorded for acoustic analysis. In the preparation of our corpus, it was created a narrative text in English, ten assertive sentences in English and ten in Portuguese. This corpus was read by the informants and analyzed under PRAAT free software in order to obtain values for duration, pitch and amplitude parameters. The results show that, unlike the Americans, there is no favoring to stress retraction from Brazilian speakers when facing stress clash environment - either in the phonological phrases in English or Portuguese - but rather, pause insertion for the preservation of the principle of euphonic rhythmic type that is Brazilian Portuguese inserted in. Our data also point to a strong influence of American English in the production of BP as second language with respect to the stress clash resolution strategies, at which, contrary to the trend of the BP, Americans use the strategy of stress retraction.